Wealth in Couples: Introduction to the Special Issue - Philipp M. Lersch; Emanuela Struffolino; Agnese Vitali (European Journal of Population, 2022)
The assumption that economic resources are equally shared within households has been found to be untenable for income but is still often upheld for wealth. In this introduction to the special issue "Wealth in Couples", we argue that within-household inequality in wealth is a pertinent and under-researched area that is ripe for development. To this end, we outline the relevance of wealth for demographic research, making the distinction between individual and household wealth. Drawing on a life-course perspective, we discuss individual wealth accumulation within couples and its links to family-demographic processes, the institutional context, and norms on pooling and sharing. We conclude with a brief summary of the main findings from the special issue and highlight implications for demographic research and for future research in this field.
Keywords: 300; Wealth; Couples; Life course; Gender; Inequality; Partners